2009
DOI: 10.1007/s10867-009-9164-x
|View full text |Cite
|
Sign up to set email alerts
|

Green light effects on biological systems: a new biophysical phenomenon

Abstract: This paper reports a new phenomenon connected with the influence of green light (GL) on biological systems. Our experiments have revealed an antioxidant effect of GL on cells subjected to lethal doses of UV at the cellular level and a protective effect of GL on DNA denatured by UV, coupled with a structural modification of DNA macromolecules under GL irradiation, at the molecular level. Mouse melanocyte cultures are subjected to UV irradiations with L(50) fluxes of 16.0 J m(-2) s(-1). GL is obtained from a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Interestingly, the Pi-mCherry line also displayed some increased growth when cultured under blue light. It has been previously reported that blue-green light may have antioxidant effects (Comorosan et al, 2009), have protective effects on protein subjected to UV irradiation (Espinoza and Mercado-Uribe, 2017), and initiate biophysical processes in cells such as increased wound healing and cell proliferation (Adamskaya et al, 2011;Rohringer et al, 2017).…”
Section: Optogenetic Engineering Of Pi-myc Creates a Fast Functional Form Of Myc For Initiating Acute Onset Of Overexpression In Living Cmentioning
confidence: 99%
“…Interestingly, the Pi-mCherry line also displayed some increased growth when cultured under blue light. It has been previously reported that blue-green light may have antioxidant effects (Comorosan et al, 2009), have protective effects on protein subjected to UV irradiation (Espinoza and Mercado-Uribe, 2017), and initiate biophysical processes in cells such as increased wound healing and cell proliferation (Adamskaya et al, 2011;Rohringer et al, 2017).…”
Section: Optogenetic Engineering Of Pi-myc Creates a Fast Functional Form Of Myc For Initiating Acute Onset Of Overexpression In Living Cmentioning
confidence: 99%
“…Meanwhile, some researchers have suggested that when insects are exposed to UV irradiation, biological characteristics of these insects can be changed, because of damaging cells or DNAs of the body by reactive oxygen species (ROS) produced by UV irradiation (Zhang et al ., 2011; Ali et al ., 2016). However, in an animal body, green light illumination results in an antioxidant role on cells subjected to lethal doses of UV, in addition to, and has a protective role on DNAs denatured by UV light (Comorosan et al ., 2009). The green light illumination could result in weak oxidative stress in M. separata moths, and the moths under this light could restore the damage caused by this light stress (Kim et al ., 2018 b ).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of its dielectric properties (i.e. dielectric constant, loss and conductivity) and the amount of energy absorbed by the blood, which is quantified using a measure called the specific absorption rate (SAR), is very important in the domain of nano-medicine and for rapid laser diagnosis and better therapeutic purposes [4,5,17]. Dielectric properties are the inherent molecular properties present in all materials capable of impeding electron movement and hence creating polarization within the substance.…”
Section: Introductionmentioning
confidence: 99%